A Mixed-Methods Realist Evaluation of the Implementation and Impact of Community Forensic CAMHS to Manage Risk for Young People With Forensic and Mental Health Needs: Study Protocol - Lane, Rebecca; D'Souza, Sophie; Livanou, Maria; Jacob, Jenna; Riches, Wendy; Ullman, Roz; Rashid, Anisatu; Singleton, Rosie; Wheeler, James; Fuggle, Peter; Bevington, Dickon; Deighton, Jessica; et al. (Frontiers in Psychiatry, 2021)
Introduction: Young people in contact with forensic child and adolescent mental health services present with more complex needs than young people in the general population. Recent policy has led to the implementation of new workstreams and programmes to improve service provision for this cohort. This paper aims to present the protocol for a national study examining the impact and implementation of Community Forensic Child and Adolescent Mental Health Services (F:CAMHS). Methods and analysis: The study will use a mixed-methods Realist Evaluation design. Quantitative service activity and feedback data will be collected from all 13 sites, as well as questionnaires from staff. Non-participant observations and qualitative interviews will be conducted with staff, young people and parents/guardians from four focus study sites. An economic evaluation will examine whether Community F:CAMHS provides good value for money. The results will be triangulated to gain an in-depth understanding of young people’s, parents/guardians’ and staff experiences of service. Ethics and dissemination: Ethical approval was granted by the Health Research Association and UCL Ethics. The results will be disseminated via project reports, feedback to sites, peer-reviewed journal publications and conference presentations.